Renal Artery Stenosis and Ipsilateral Renal Cell Carcinoma: Description of an In Situ Partial Nephrectomy and Splenorenal Arterial Bypass - Scott A. Slavis; George S. Ganesan; Claudia Swift; Ronald C. Ruppert (The Scientific World Journal)
A case of a renal artery stenosis and ipsilateral renal cell carcinoma with long term results is reported. A 65-year-old man with renovascular hypertension, renal insufficiency, and nephrotic range proteinuria presented with an incidental renal cell carcinoma. Concomitant in situ left partial nephrectomy and splenorenal arterial bypass was achieved. The patient is doing well without evidence of malignancy, stable renal function, markedly improved proteinuria and stable blood pressure more than three years later. The techniques of this procedure are detailed and underscore the possibility of successful removal of a renal cell carcinoma with preservation of renal function despite renal artery stenosis.